Enkorten – A Potential Drug for the Treatment of Rheumatoid Arthritis - Mulabegović, Nedžad; Kusturica, Jasna; Todić-Rakanović, Maida; Mijanović, Mirjana; Bečić, Fahir; Začiragić, Asija; Škrbo, Selma; Burnazović-Ristić, Lejla; Kulo, Aida; Loga-Zec, Svjetlana (IntechOpen, 2012)
None